Closed Reduction for the Treatment of Grade IV Supination‐External Rotation Fracture of the Ankle Joint: A Retrospective Analysis - Hong‐zhou Zhao; Tong‐shun Fan; Shu‐li Wang; Li‐min Liu; Ming‐jun Liu; Jia‐hui Xing (Orthopaedic Surgery, 2021)
Objective To investigate the curative effect of closed reduction and external fixation in the treatment of grade IV supination‐external rotation fractures of the ankle joint. Methods Fifty‐six patients treated with closed reduction and external fixation from February 2016 to March 2020 were included in this retrospective study, all with sprains. After receiving nerve block anesthesia, the patient underwent closed reduction under C‐arm fluoroscopy, and the ankle joint was fixed in a dorsiflexion‐inversion position with casting and splints after the end of the fracture met the reduction standard by fluoroscopy. One week and four weeks after the reduction treatment, oblique axial and coronal MR scans of the ankle joint were performed to determine the degree of injury and healing of the inferior tibiofibular syndesmosis; anteroposterior and lateral X‐rays of the ankle joint (including the ankle acupoints) were regularly reviewed to observe the fracture alignment and healing. Combined with the images and physical examination, the patients were instructed to undergo ankle weight‐bearing rehabilitation training when they met the clinical healing standard, and at the last follow‐up, the Mazur ankle evaluation and grading system were used for evaluation. After the reduction, the images were evaluated according to the Leeds standard. The image healing of fracture was evaluated by callus growth criteria. Results The follow‐up period of patients ranged from 11 to 58 months, with an average of 26.8 months. The clinical healing time was (8.51 ± 2.12) weeks. The excellent and good rating after reduction was 82.1%, and the excellent and good rating during clinical fracture healing was 73.2%, according to the Leeds imaging evaluation. According to the Mazur ankle evaluation and grading system, the excellent and good rating was 75.0%. Pairwise comparison of callus images at 4, 6 and 12 weeks showed statistically significant differences (P < 0.05), suggesting callus growth at different time periods. A total of 56 patients had anterior inferior tibial fibular ligament (AITFL) injuries (grade II‐III), among which 11 patients had AITFL injuries combined with grade II injuries of the interosseous ligament (IOL) and 4 patients had AITFL injuries combined with grade III injuries of the IOL. Conclusions Most of the patients with grade IV supination‐external rotation fracture of the ankle joint had good prognosis after closed reduction and plaster combined with splint fixation. For patients with IOL injury who had poor prognosis, open reduction and internal fixation therapy is appropriate.